2012
DOI: 10.1093/infdis/jis594
|View full text |Cite
|
Sign up to set email alerts
|

The Nonsteroidal Antiinflammatory Drug Diclofenac Potentiates the In Vivo Activity of Caspofungin Against Candida albicans Biofilms

Abstract: In this study, we demonstrated that in vitro Candida albicans biofilms grown in the presence of diclofenac showed increased susceptibility to caspofungin. These findings were further confirmed using a catheter-associated biofilm model in rats. C. albicans-inoculated catheters retrieved from rats that were treated with both diclofenac and caspofungin contained significantly fewer biofilm cells and showed no visible biofilms inside the catheter lumens, as documented by scanning electron microscopy, as compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 20 publications
1
53
0
2
Order By: Relevance
“…Sodium Diclofenacshowed lower MIC against C. albicans and C. glabrata while ibuprofen showed lower MIC against C. krusei in comparison to other NSAIDs. By testing their effect on germ tube formation, it was found that Sodium Diclofenacat 500 µg/ml inhibit germ tube formation while ketoprofen and ibuprofen inhibit it to lesser extent that agree with many studies [40,41,42].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Sodium Diclofenacshowed lower MIC against C. albicans and C. glabrata while ibuprofen showed lower MIC against C. krusei in comparison to other NSAIDs. By testing their effect on germ tube formation, it was found that Sodium Diclofenacat 500 µg/ml inhibit germ tube formation while ketoprofen and ibuprofen inhibit it to lesser extent that agree with many studies [40,41,42].…”
Section: Discussionsupporting
confidence: 86%
“…The second study [42] showed inhibition of the yeast-to-hyphae transition by diclofenac on solid YPD media. The first study demonstrated a significant reduction of biofilm formation in YPD on small polyvinyl chloride disks by diclofenac when added during the period of adhesion and biofilm formation, quantified by XTT measurements.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the currently available antifungals and antibiotics are unable to cure these biofilm-associated infections effectively (11,12). Therefore, treatment often requires the removal of the infected device, which can be an expensive and painful surgical procedure.…”
mentioning
confidence: 99%
“…To this end, E. coli were grown in tryptone broth medium in the presence or absence of amoxicillin as positive control, NSAIDs and Amoxicillin combined with aspirin for 24 h. The bacterial culture was incubated with ethidium bromide for 20 min at room temperature in the dark. Membrane permeability was (Bink et al, 2012).…”
Section: Membrane-permeability Assaymentioning
confidence: 99%